VISITOR’S PERCEPTION OF PAGILARAN TEA GARDEN AGROTOURISM - Muhammad Aulia Rachman; Kadhung Prayoga; Joko Mariyono (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Visitors to tourism objects have the motivation and perception of traveling. Therefore, a study is needed to analyze visitors' perceptions that arise from the visitors and the push and pull factors that influence the motivation of visitors to the Pagilaran Tea Garden Agrotourism. This study aims to analyze the perceptions and motivations that develop in the decisions of visitors when traveling, as well as to analyze the influence of perceptions, motivations, age, education, income, distance, and gender on the interest in revisiting. The research was conducted in March 2022 at Pagilaran Tea Garden Agrotourism, Keteleng Village, Blado District, Batang Regency, Central Java. The research method used is descriptive quantitative research by distributing questionnaires to 97 respondents selected by the incidental sampling method. The perception data analysis technique is frequency tabulation using Likert scale scoring with a number line, motivation data with the Guttman scale, and ordinary least square techniques using the SPSS application software. The study found that visitors were satisfied based on a perception score of 74% and a motivation score of 85%. Of the variables perception, motivation, age, education, income, distance, and gender, obtained from multiple linear regression tests, income and gender variables have positive values on the F test for all variables that affect the interest in revisiting, as well as on the results of the t-test. It stated that only perception, income, and distance variables were significant.